Beyond the Safe-Haven Narrative: Investment Knowledge, Risk Perception, and Household Gold Investment Decisions in Lamongan, Indonesia - Sevia musfita Neysa; Ahmad Munir Hamid; Huril A’ini (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
Gold remains one of the most culturally familiar and financially trusted investment instruments among Indonesian households. However, the common explanation that households buy gold solely because it is a safe-haven asset is, from an analytical perspective, still incomplete. This study revises and strengthens the original paper by examining how investment knowledge and risk perceptions influence households’ decisions to invest in gold in Lamongan, East Java. Using a qualitative descriptive design, this study analyzes households’ investment narratives as well as supporting institutional data from Pegadaian Lamongan. Empirical patterns show a significant increase in gold savings activity: gold savings rose from 5,659 grams in 2023 to 16,849 grams as of April 14, 2026, while the number of active customers increased from 2,923 to 5,359 during the same period. These figures indicate that gold has become more than just a traditional store of wealth; it is increasingly being used as a practical financial planning tool. The study’s findings suggest that household decisions are influenced by three interrelated mechanisms. First, investment knowledge enables households to distinguish gold from regular savings, evaluate price fluctuations, understand the bid-ask spread, and choose between physical and digital gold products more carefully. Second, risk perception does not always hinder investment; rather, it filters the type, timing, and channels of gold investment. Third, household decisions are socially embedded through family discussions, intergenerational experiences, and trust in formal institutions. This study contributes to the fields of behavioral finance and Planned Behavior Theory by demonstrating that the perceived value of gold as a safe haven is translated into household actions through perceptions of control, practical knowledge, and socially constructed risk. Policy implications highlight the need for targeted financial education that not only explains the benefits of gold but also addresses liquidity costs, price volatility, storage security, digital platform risks, and portfolio diversification.